Applying the Mumtaz Method as a Linguistic Strategy to Foster Arabic Syntax (Nahwu) Mastery - Amelia, Riska; Wahyudin, Wahyudin; Rosmiati, Rosmiati; Abna, Nurjannah; Syahid, Akhmad (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
The teaching of Arabic grammar (nahwu) often poses challenges for students due to its abstract rules and memorization demands, which frequently result in low levels of comprehension and achievement. This study aims to address these challenges by examining the effectiveness of the Mumtaz Method in enhancing students’ understanding of nahwu. The research employed a Classroom Action Research (CAR) framework to systematically reflect upon and improve classroom practices based on iterative observations and evaluations. The participants were students of class C2 at Madrasah Ibtidaiyah (MI) Idadiyah Campus III Putri DDI Mangkoso, Soppeng Riaja District, Barru Regency. The Mumtaz Method, which adapts familiar melodies such as religious and children’s songs into learning media, was applied to facilitate the memorization and internalization of Arabic grammatical structures. The study was carried out over two cycles, following the stages of pre-cycle (initial reflection), Cycle I, and Cycle II. The findings demonstrated a notable improvement in students’ comprehension of nahwu. The average score increased from 61.90 with a completion rate of 33% at the pre-cycle stage to 68.09 with 52% completion in Cycle I, and further to 77.38 with a 96% completion rate in Cycle II. These results confirm the effectiveness of the Mumtaz Method in improving Arabic syntax learning. The study contributes to applied linguistics and language pedagogy by offering an innovative, culturally relevant strategy to support grammar acquisition in young learners.